Implementation of Qanun Gayo Lues Number 15 of 2013 Concerning Regional Spatial Planning in the Field of Agricultural Areas - Rajemi Rajemi*; Dahlan A. Rahman; Darmanto Darmanto (Universitas Syiah Kuala, 2024)
The Qanun of the Spatial Planning Plan of Gayo Lues Regency Number 15 of 2013 in the agricultural sector was prepared as a basis for the development and development of agricultural areas in Gayo Lues Regency. The purpose of this study was to analyse the implementation of the Qanun RTRW of 2013 in Gayo Lues Regency by focusing on agricultural designation areas and obstacles in implementing it. The theory used is the theory of policy implementation according to Edward III with four implementation indicators including communication, resources, disposition and bureaucratic structure. The type of research uses a qualitative descriptive approach. The results of the study indicate that the Implementation of the Qanun RTRW of 2013 in Gayo Lues Regency is still not optimal. This is caused by the inconsistent spatial planning with the use of space, the inconsistent spatial planning with planning documents, and the less than optimal participation of the Community in the use and utilization of Agricultural Areas. Obstacles in implementing the Qanun RTRW of Gayo Lues Regency in 2013 include the absence of a strong political commitment from the local government in terms of providing an adequate budget, simplifying regulations, lack of coordination between related government agencies and low public awareness.